Calcium-Sensing Receptors of Human Neural Cells Play Crucial Roles in Alzheimer's Disease - Chiarini, Anna; Armato, Ubaldo; Liu, Daisong; Dal Prà, Ilaria (Frontiers in Physiology, 2016)
In aged subjects, late-onset Alzheimer’s disease (LOAD) starts in the lateral entorhinal allocortex where a failure of clearance mechanisms triggers an accumulation neurotoxic of amyloid-β42 oligomers (Aβ42-os). In neurons and astrocytes, Aβ42-os enhance the transcription of Aβ precursor protein (APP) and β-secretase/BACE1 genes. Thus, by acting together with γ-secretase, the surpluses of APP and BACE1 amplify the endogenous production of Aβ42-os which pile up, damage mitochondria, and are oversecreted. At the plasmalemma, exogenous Aβ42-os bind neurons' and astrocytes' calcium-sensing receptors (CaSRs) activating a set of intracellular signalling pathways which upkeep Aβ42-os intracellular accumulation and oversecretion by hindering Aβ42-os proteolysis. In addition, Aβ42-os accumulating in the extracellular milieu spread and reach mounting numbers of adjacent and remoter teams of neurons and astrocytes which in turn are recruited, again via Aβ42-osCaSR-governed mechanisms, to produce and release additional Aβ42-os amounts. This relentless self-sustaining mechanism drives AD progression towards upper cortical areas. Later on accumulating Aβ42-os elicit the advent of hyperphosphorylated (p)-Tau oligomers which acting together with Aβ42-os and other glial neurotoxins cooperatively destroy wider and wider cognition-related cortical areas. In parallel, Aβ42-osCaSR signals also elicit an excess production and secretion of nitric oxide and vascular endothelial growth factor-A from astrocytes, of Aβ42-os and myelin basic protein from oligodendrocytes, and of proinflammatory cytokines, nitric oxide and (likely) Aβ42-os from microglia. Activated astrocytes and microglia survive the toxic onslaught, whereas neurons and oligodendrocytes increasingly die. However, we have shown that highly selective allosteric CaSR antagonists (calcilytics), like NPS 2143 and NPS 89626, efficiently suppress all the neurotoxic effects Aβ42-osCaSR signalling drives in cultured cortical untransformed human neurons and astrocytes. In fact, calcilytics increase Aβ42 proteolysis and discontinue the oversecretion of Aβ42-os, nitric oxide, and vascular endothelial growth factor-A from both astrocytes and neurons. Seemingly, calcilytics would also benefit the other types of glial cells and cerebrovascular cells otherwise damaged by the effects of Aβ42-osCaSR signalling. Thus, given at amnestic minor cognitive impairment (aMCI) or initial symptomatic stages, calcilytics could prevent or terminate the propagation of LOAD neuropathology and preserve human neurons' viability and hence patients’ cognitive abilities.